Efficient callus induction and regeneration in proso millet. (28th August 2021) - Liu, Beibei; Wu, Huiqin; Yang, Simin; Wu, Enguo; Yang, Pu; Gao, Xiaoli
Abstract: Proso millet ( Panicum miliaceum L.) is an important drought‐tolerant crop, and recently it has become a research focus because of its health‐care and nutrition significance. A study was carried out to investigate callus induction and differentiation and plantlet rooting in Shaanmi 1 and Shaanmi 2 with young leaves of the two varieties. Its result showed that in proso millet, the age of aseptic seedlings could influence on inducing calli from young leaves with the highest callus induction frequency at the seedling age of 7 d. N6 medium performed better in inducing calli from young leaves. There did appear to be no calli on MS medium without 2, 4‐D, but calli were induced on N6 medium without 2, 4‐D in Shaanmi 2, with its induction frequency standing 6.45% and no calli were induced on the medium without 2, 4‐D in Shaanmi 1 . With 2, 4‐D added, there appeared the highest callus induction frequency at a 2, 4‐D concentration of 3.0 mg L –1 . The optimal medium to induce calli from young leaves in proso millet was N6 medium plus 2, 4‐D (3.0 mg L –1 ) and KT (0.5 mg L –1 ), with its callus induction frequency at 64.33% ( Shaanmi 1 ) and 68.67% ( Shaanmi 2 ), respectively. The optimal callus differentiation medium was MS medium plus 1.0 mg L –1 6‐BA and 0.5 mg L –1 NAA, with its differentiation rate at 87.78% ( Shaanmi 1 ) and 96.29% ( Shaanmi 2 ), respectively. Proline adding at 600 mg L –1 was conducive to callus differentiation. The optimal rooting medium was 1/2MS medium plus NAA (0.1 mg L –1 ), with its rooting rate at 100%. Core Ideas: This study explored the optimal conditions for callus induction with young leaves as explants. The optimum conditions for callus differentiation and plant regeneration of millet were studied. This study established efficiency regeneration system of millet and laid a foundation for further research.